(untitled) (Bangladesh Journal of Botany, 2018)
An efficient protocol was developed for in vitro mass propagation of Paulownia tomentosa (Thunb.) Steud. using shoot tip and leaf segment explants from field grown plant. Different concentrations and combinations of BAP, Kn, zeatin and NAA were used for multiple shoot regeneration. Among two types of explants, leaf segment produced the highest number of shoots per explant (12 ± 0.4) when they were cultured on MS supplemented with 3.0 mg/l Kn and 0.5 mg/l NAA. Addition of 10% CW to above mentioned medium increased the number of shoots (18) per culture. Shoot tip explants also produced multiple shoots in the same medium, but their performance was not good as leaf segment explants. For shoot elongation, 100 mg/l urea was more effective when added with best shoot induction medium. Shoots rooted well in halfstrength MS supplemented with 2.0 mg/l NAA, within 12 - 15 days. Regenerated plantlets were successfully acclimatized and established in poly bag containing a mixture of soil and compost in 2:1 ratio. About 90% plantlets survived under open field conditions.